Traumatic Macular Hole: Diagnosis, Natural History, and Management - Greg Budoff; Neelakshi Bhagat; Marco A. Zarbin (Journal of Ophthalmology)
Traumatic macular hole occurs most often in young men and can present after various types of injuries. Traumatic macular holes result from anteroposterior and tangential vitreoretinal traction and may exhibit concurrent additional pathologies such as Berlin’s edema and subretinal fluid. Optical coherence tomography can play an essential role in patient management both at presentation and during follow-up. Initial management consists of observation, but macular hole repair can be performed if spontaneous resolution does not occur. Upon macular hole closure, vision may improve, on average, by two lines or more but may be limited by associated macular pathology.